The Big Drink Debate: perceptions of the impact of price on alcohol consumption from a large scale cross-sectional convenience survey in north west England - Briant Linford; Harkins Corinne; Morleo Michela; Phillips-Howard Penelope A; Cook Penny A; Bellis Mark A (BMC, 2011)
Abstract Background A large-scale survey was conducted in 2008 in north west England, a region with high levels of alcohol-related harm, during a regional 'Big Drink Debate' campaign. The aim of this paper is to explore perceptions of how alcohol consumption would change if alcohol prices were to increase or decrease. Methods A convenience survey of residents (≥ 18 years) of north west England measured demographics, income, alcohol consumption in previous week, and opinions on drinking behaviour under two pricing conditions: low prices and discounts and increased alcohol prices (either 'decrease', 'no change' or 'increase'). Multinomial logistic regression used three outcomes: 'completely elastic' (consider that lower prices increase drinking and higher prices decrease drinking); 'lower price elastic' (lower prices increase drinking, higher prices have no effect); and 'price inelastic' (no change for either). Results Of 22,780 drinkers surveyed, 80.3% considered lower alcohol prices and discounts would increase alcohol consumption, while 22.1% thought raising prices would decrease consumption, making lower price elasticity only (i.e. lower prices increase drinking, higher prices have no effect) the most common outcome (62%). Compared to a high income/high drinking category, the lightest drinkers with a low income (adjusted odds ratio AOR = 1.78, 95% confidence intervals CI 1.38-2.30) or medium income (AOR = 1.88, CI 1.47-2.41) were most likely to be lower price elastic. Females were more likely than males to be lower price elastic (65% vs 57%) while the reverse was true for complete elasticity (20% vs 26%, P < 0.001). Conclusions Lower pricing increases alcohol consumption, and the alcohol industry's continued focus on discounting sales encourages higher drinking levels. International evidence suggests increasing the price of alcohol reduces consumption, and one in five of the surveyed population agreed; more work is required to increase this agreement to achieve public support for policy change. Such policy should also recognise that alcohol is an addictive drug, and the population may be prepared to pay more to drink the amount they now feel they need.